Operations research and enterprise systems : third International Conference, ICORES 2014, Angers, France, March 6-8, 2014, Revised selected papers /: third International Conference, ICORES 2014, Angers, France, March 6-8, 2014, Revised selected papers. (2015) - Unknown
No abstract available